Penerapan Sistem Pengendalian Internal dan Implikasinya terhadap Efektivitas Penyaluran Kredit pada Lembaga Perkreditan Desa - Ardyani, Ni Putu Evi; Suarmanayasa, I Nengah (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This research aimed at examining the effect of internal controlling system’s elements consisted of controlling environment, risk assessment, information and communication, controlling activity, and monitoring activity towards the effectiveness of credit distribution in the local bank or known as LPD in Busungbiu District, Buleleng Regency. This present study used causal qualitative research design. The data used in this research was a primer data and was collected by using questionnaire. The sampling used in this research was saturated sampling technique. There were 10 active local banks or known as LPD in Busungbiu District used as the sample of this research. The result of this research revealed that the controlling environment, risk assessment, information and communication, and monitoring activity contributed a significant and positive effect towards the effectiveness of the local bank credit distribution, meanwhile, the controlling activity contributed a negative effect towards the effectiveness of local bank credit distribution.